The effect of baseline serum uric acid on chronic kidney disease in normotensive, normoglycemic, and non-obese individuals: A health checkup cohort study. - Young-Bin Son; Ji Hyun Yang; Myung-Gyu Kim; Sang Kyung Jo; Won Yong Cho; Se Won Oh (PLoS ONE, 2021)
Introduction The independent role of serum uric acid (SUA) on kidney disease is controversial due to its association with metabolic syndrome. The objective of this study was to investigate the association of baseline SUA with development of chronic kidney disease and eGFR decline in normotensive, normoglycemic and non-obese individuals during follow up period. Materials and methods We included non-hypertensitive, non-diabetic, and non-obese 13,133 adults with estimated glomerular filtration rate (eGFR) ≥ 60ml/min/1.73m2 who had a voluntary health check-up during 2004-2017. Results SUA was positively related to adjusted means of systolic blood pressure (SBP), triglyceride, body mass index, and body fat percent. SUA was inversely associated with high density lipoprotein HDL (P for trend ≤0.001). SUA was an independent risk factor for the development of diabetes, hypertension, and obesity. During 45.0 [24.0-76.0] months of median follow up, the highest quartiles of SUA showed significant risks of 30% eGFR decline compared than the lowest quartile (RR:3.701; 95% CI: 1.504-9.108). The highest quartile had a 2.2 fold (95% CI: 1.182-4.177) increase in risk for incident chronic kidney disease (CKD). Conclusions SUA is an independent risk factor for the development of diabetes, hypertension, and obesity in the healthy population. High SUA is associated with increased risk of CKD development and eGFR decline in participants with intact renal function.